Aggregation and sedimentation of shattered graphene oxide nanoparticles in dynamic environments: a solid-body rotational approach. Issue 8 (24th July 2018) - Babakhani, Peyman; Bridge, Jonathan; Phenrat, Tanapon; Doong, Ruey-an; Whittle, Karl R.
Abstract : Nanoparticle (NP) aggregation is typically investigated in either quiescent or turbulent mixing conditions; neither is fully representative of dynamic natural environments. Abstract : Nanoparticle (NP) aggregation is typically investigated in either quiescent or turbulent mixing conditions; neither is fully representative of dynamic natural environments. In groundwater, complex interacting influences of advective–diffusive transport, pore tortuosity, and the arrival of aggregates from up-gradient pores impacts the aggregation behaviour of NPs, whereas in surface waters, continuous mixing of fresh particle and aged aggregate populations amends aggregation rates. To mimic such conditions, a cylinder reactor containing shattered graphene oxide NP (<100 nm) suspension was set to rotate with a Reynolds number (Re) close to one and with zero shear. Two main aggregation phases were then observed. Up to 250–350 min, NP remained near the rotational axis longer than in static conditions, giving rise to higher aggregation rates interpreted as an enhanced perikinetic aggregation and differential sedimentation due to mixing with resuspending aggregates. In this phase, a population-balance model estimated an attachment efficiency >5 times in the rotating system than in the static system. Later (5–13 h) aggregates collided with extensively each other, broke, and reformed on the rotating cylinder wall giving rise to larger, denser aggregates (>1 cm). These results thus shed new light on the differences in aggregation behaviour between porous media and other natural environmental systems compared to quiescent batch experiments.